hypotensive anesthesia - Safar, Petyer (1955)
We have discussed the different techniques of hypotensive anesthesia and physiological bases. The technique used by us in the first 53 operations are written in detail. Fundamentally the Enderby was using Hexamethonio bromide and combined postural ischemia. Our observations were analyzed. The data reported here include measurement of blood loss and the gravimetric technique was compared with those conducted under normotensive anesthesia. A group of 40 radical mastectomies was subjected to properly controlled conditions in a comparative study to assess to what extent - if at all - such typical operations are aided by controlled hypotension.